2
$\begingroup$

As the title states, for complex $z$ I want to show $\cos(z+ \pi) = -\cos(z)$.

My first attempt was to change $\cos$ into $(e^{iz} + e^{-iz}) /2$ but then I figured using the identity $\cos(z) = \cos(x)\cosh(y)+i\sin(x)\sinh(y)$ was better since $\cos(x+ \pi)=-\cos(x)$ for real $x$. But now I'm unsure how to proceed.

$\endgroup$
  • $\begingroup$ The easiest way is to use the principle of permanence, but this principle is not trivial. $\endgroup$ – lhf Sep 30 '15 at 3:02
2
$\begingroup$

Hint: Recall that $e^{\pi i} = e^{-\pi i} = -1$ and that $e^{u+v} = e^{u}e^{v}$ and go with your first way.

$\endgroup$
1
$\begingroup$

In both cases you must get the same answer. For instance, with the second one we have, for $z=x+iy$, \begin{align} \cos(z+\pi)&=\cos(x+\pi+iy)\\ &=\cos(x+\pi)\cosh y+i\sin(x+\pi)\sin y\\ &=(\cos x\cos\pi-\sin x\sin \pi)\cosh y+i(\sin x\cos \pi +\sin\pi\sin x)\sinh y\\ &=\left[(\cos x)(-1)-(\sin x)(0)\right]\cosh y+i[(\sin x)(-1)+(0)\cos x]\sinh y\\ &=-\cos x\cosh y-i\sin x\sinh y \tag 1 \end{align} Added:

Now, $$-\cos z=-(\cos x\cosh y+i\sin x\sinh y)=-\cos x\cosh y-i\sin x\sinh y\tag 2$$

By comparing ($1$) and ($2$) the identity follows.

$\endgroup$
  • $\begingroup$ But isn't that -(cos$x$cosh$y$+isin$x$sinh$y$)? $\endgroup$ – Lupin Sep 30 '15 at 3:14
  • $\begingroup$ Which is different from -(cos$x$cosh$y$-sin$x$sinh$y$)? $\endgroup$ – Lupin Sep 30 '15 at 3:14
  • $\begingroup$ @Lupin: I don't understand what are you asking. $\endgroup$ – Ángel Mario Gallegos Sep 30 '15 at 3:15
0
$\begingroup$

The sleek, more complex-analytic way to do it: Let $f(z) = \cos z + \cos(z+\pi)$. Then $f$ is entire, and $f(x) = 0$ for $x \in \mathbb{R}$. Hence, by the identity theorem, $f(z) = 0$ for all $z \in \mathbb{C}$.

$\endgroup$
  • $\begingroup$ That's the principle of permanence... $\endgroup$ – lhf Oct 1 '15 at 1:46
0
$\begingroup$

Just continue your approach:

$\cos(z) = \cos(x)\cosh(y)+i\sin(x)\sinh(y)$

Then just plug in $z+\pi$ instead:

$\cos(z+\pi) = \cos(x+\pi)\cosh(y)+i\sin(x+\pi)\sinh(y)$

And observe that both $\cos(x+\pi)=-\cos(x)$ and $\sin(x+\pi)=-\sin(x)$ and you get:

$\cos(z+\pi) = -\cos(x)\cosh(y)-i\sin(x)\sinh(y) = -\cos(z)$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.